Analog lightwave links for detector front-ends at the LHC - Baird,A; Dowell,J; Duthie,P; Gill,K; Glick,M; Green,NP; Hall,G; Halsall,R; Jarlskog,G; Kennedy,L; Kenyon,I; Moseley,AJ; et al. (1995)
Lightwave links are being developed for volume application in the transfer of analog signals from the tracking detector front-ends to the readout electronics. The links are based on electro-optic intensity modulators which are mounted on detectors and connected by optical fibers to remotely located transceivers (lasers and photoreceivers). The modulators are III-V semiconductor reflective devices based on multi-quantum well structures. The transceivers will be integrated devices of a novel design. Modulator prototypes have been fabricated and tested. Neutron and γ-ray irradiation studies have been performed on modulators and fibers. The main results achieved so far are reported. This work is part of the CERN DRDC project RD23 [1].